Consumer behavior regarding wearable technologies: Google Glass - Gibran Sales Nunes; Emílio José Montero Arruda Filho (Innovation & Management Review, 2018)
Purpose: This purpose of this study is to analyze consumer behavior in relation to Google Glass. The study considers the adoption and diffusion of the innovation, aspects related to technological convergence and the theories of utilitarian, hedonic and social value. Design/methodology/approach: This qualitative, exploratory study uses the methodological approach of netnography via passive observation. Data collection was conducted using the social network Reddit over a period of about four months. Findings: Three categories and two subcategories of consumers were found, namely, socially satisfied; socially constrained; and early adopters, divided into enthusiasts and visionaries. Research limitations/implications: A limitation of this research pertains to the data collected regarding consumption preferences of users and potential adopters. No questions were created, but rather, discussions were selected, from the social network Reddit, that focused on factors pertaining to the theories studied. Practical implications: The research brings an important insight regarding the launch of new products: to obtain a good market position for new devices, failures or inadequate perceptions that will negatively impact the technology's dissemination must be minimized. Social implications: This study presents social value of technological consumption as a function of the conspicuousness, status and position of users who own devices that differ from those commonly available on the market. Originality/value: This study reveals which elements exert the greatest influence on intention to consume so-called wearable technology. In particular, it analyzes consumer behavior in relation to Google Glass, evaluating the reasons that were perceived as positive and negative for consumers which blocked the technology launch in the market.
Keywords: 650; Social identity; Consumer behaviour; Netnography; Wearable technology; Google Glass